MENINGKATKAN KEMAMPUAN MENULIS BAHASA INGGRIS NARRATIVE TEXT DENGAN MEDIA GAMBAR BERSERI PADA SISWA KELAS X IB2 SMA NEGERI 2 MAUMERE - ANTONIA BLAANG (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
In the classroom, students often complain and say it is difficult if the teacher give themthe task to write in English. The students would say they could not do it even when theyhaven’t begun yet. They do not have self-confident, feeling afraid of doing wrong, do notknow what to write and how to get started. For those reasons the teacher conduct ClassAction Research using images Pinocchio and Cinderella as a medium of teaching on learningto write Narrative Text. The results showed that the use of images media is able to increasethe students’ ability to write narrative text in English class X IB2 at SMA Negeri 2 Maumere.For increasing the students’ excitement in gaining an idea of writing a story narrative, theauthors advise teachers to use images in the form of picture books, comic books, or comicstrips, newspaper story as a source of inspiration.